Application of Fe2O3 nanoparticles improves the growth, antioxidant power, flavonoid content, and essential oil yield and composition of Dracocephalum kotschyi Boiss. - Khanizadeh, Parisa; Mumivand, Hasan; Morshedloo, Mohamad Reza; Maggi, Filippo (Frontiers in Plant Science, 2024)
Dracocephalum kotschyi Boiss., an endemic and endangered medicinal and aromatic plant in Iran, showcases distinct botanical characteristics and therapeutic promise. According to the IUCN grouping criteria, this plant is facing challenges due to overcollection from its natural habitats. To address this issue, there is an increasing inclination towards cultivating this species within agricultural systems. This study aimed to evaluate the impact of applying Fe2O3 nanoparticles (NPs) at varying concentrations (50, 100, and 200 mg L-1), as well as bulk Fe2O3 at the same concentrations, on the growth, essential oil production, antioxidant capacity, total phenol, and flavonoid content of D. kotschyi. The foliar application of 100 and/or 200 mg L-1 of Fe2O3 NPs resulted in the greatest leaf length and dry weight, while Fe2O3 NPs at the level of 100 mg L-1 led to the highest leaf/stem ratio. Additionally, spraying 200 mg L-1 of Fe2O3 NPs and all concentrations of bulk Fe2O3 positively impacted chlorophyll and carotenoid levels. Both nano and bulk Fe2O3 supplements stimulated H2O2 production and subsequently enhanced enzymatic antioxidant activity. The use of 50 mg L-1 of Fe2O3 NPs resulted in the highest flavonoid content and non-enzymatic antioxidant activity. Meanwhile, the highest essential oil content and yield was achieved by the application of 50 and/or 100 mg L-1 Fe2O3 NPs. The addition of low concentration of Fe2O3 NPs (50 mg L-1) resulted in a significant increase in the concentration of geranial, while a higher supply of Fe2O3 NPs (200 mg L-1) significantly decreased the percentage of neral in the essential oil. Overall, the application of Fe2O3 NPs demonstrated significant potential for increased biomass, enhanced yield, essential oil production, and phytochemical attributes. The findings highlight the versatility of Fe2O3 NPs at optimal concentrations, acting as both a nano-fertilizer and a nano-inducer, promoting the production and accumulation of valuable secondary metabolites in plants.